Essays in environmental economics - Bezerra, Bruno Felipe Lenin Souza (2025)
This article aims to provide a study of the energy transition process through the analysis of data for developed, developing countries and BRICS. Seen the importance of the renewable energy sector in the world, it is important to analyze the main factors of the increase of this sector in the world energy matrix. To this end, we will use Dynamic OLS (DOLS) and Fully Modified OLS (FMOLS) and Canonical Cointegrating Regression (CCR) panel methods to investigate the main determinants for the renewable energy sector. The results suggest a strong relationship between globalization and the implementation of clean energy for developed countries. In addition, it is worth highlighting that for the BRICS countries, the financial market plays an important role in the adoption of a renewable energy matrix.